De Lange syndrome: subjective and objective comparison of the classical and mild phenotypes. Issue 8 (August 1997) - Allanson, J E; Hennekam, R C; Ireland, M
Abstract : Classical de Lange syndrome presents with a striking face, pronounced growth and mental retardation, and variable limb deficiencies. Over the past five years, a mild variant has been defined, with less significant psychomotor retardation, less marked pre- and postnatal growth deficiency, and an uncommon association with major malformations, although mild limb anomalies may be present. We have evaluated 43 subjects with de Lange syndrome, 30 with classical features, aged from birth to 21 years, and 13 with the mild phenotype, aged from 18 months to 30 years. In addition to assessment of gestalt and facial change with time, detailed craniofacial measurements have been obtained on each subject and composite pattern profiles compiled. The characteristic face of classical de Lange syndrome is present at birth and changes little throughout life, although there is some lengthening of the face with age and the jaw becomes squared. In mild de Lange syndrome, the characteristic classical appearance may be present at birth, but in some subjects it may be two or three years before the typical face is obvious. In general, the overall impression is less striking, perhaps because of increased facial expression and greater alertness. With age, the face loses the characteristic appearance, the nasal height increases, the philtrum does not seem as long, and the upper vermilion is full and everted, although the crescent shaped mouth with downturned corners remains. Eyebrows may be full and bushy. Objective comparison of the face in mild and classical de Lange syndrome, through the use of craniofacial pattern profiles, shows marked similarity of patterns at 4 to 9 years; both groups have microbrachycephaly, but the individual dimensions of the mild group are slightly closer to normal than their classical counterparts. The correlation coefficient is high (0.83). In the adult groups, similarity of patterns remains but is less marked. The normalisation of scores in the mild group is more dramatic. The correlation coefficient is lower (0.71). These objective findings substantiate clinical impressions of a phenotypic dichotomy. Early in life, the craniofacial features in mild de Lange syndrome may be indistinguishable from the classical phenotype and alternative discriminators must be sought in order to identify those subjects in whom the prognosis is more optimistic. Birth weight of more than 2500 g and absence of major limb anomalies may help in this regard.